Variability of the Atmospheric PM10 Microbiome in Three Climatic Regions of France - Samaké, Abdoulaye; Martins, Jean M. F.; Bonin, Aurélie; Uzu, Gaëlle; Taberlet, Pierre; Conil, Sébastien; Favez, Olivier; Thomasson, Alexandre; Chazeau, Benjamin; Marchand, Nicolas; Jaffrezo, Jean-Luc (Frontiers in Microbiology, 2021)
Primary Biogenic Organic Aerosols (PBOA) were recently shown to be produced by only a few types of microorganisms, emitted by the surrounding vegetation in the case of a regionally homogeneous field site. This study presents the first comprehensive description of the structure and main sources of airborne microbial communities associated with temporal trends in Sugar Compounds (SC) concentrations of PM10 in 3 sites under a climatic gradient in France. By combining sugar chemistry and DNA Metabarcoding approaches, we intended to identify PM10-associated microbial communities and their main sources at three sampling-sites in France, under different climates, during the summer of 2018. This study accounted also for the interannual variability in summer airborne microbial community structure (bacteria and fungi only) associated with PM10-SC concentrations during a two consecutive years’ survey at one site. Our results showed that temporal changes in PM10-SC in the three sites are associated with the abundance of only a few specific taxa of airborne fungi and bacterial. These taxa differ significantly between the 3 climatic regions studied. The microbial communities structure associated with SC concentrations of PM10 during a consecutive 2-year study remained stable in the rural area. Atmospheric concentration levels of PM10-SC species varied significantly between the 3 study sites, but with no clear difference according to site typology (rural vs urban), suggesting that SC emissions are related to regional rather than local climatic characteristics. The overall microbial beta diversity in PM10 samples is significantly different from that of the main vegetation around the urban sites studied. This indicates that the airborne microorganisms at these urban sites are not solely from the immediate surrounding vegetation, which contrasts with observations at the scale of a regionally homogeneous rural site in 2017. These results improve our understanding of the spatial behavior of tracers of PBOA emission sources, which need to be better characterized to further implement this important mass fraction of Organic Matter (OM) in Chemical Transport models (CTM).